Atomic {Pdn+-X} States at Nanointerfaces: Implications in Energy-Related Catalysis - Panagiota Stathi; Maria Solakidou; Areti Zindrou; Loukas Belles; Yiannis Deligiannakis (Energies, 2023)
Palladium is among the most versatile noble-metal atoms that, when dispersed on solid supports, can be stabilized in 0, +1, +2, +3 redox states. Moreover, despite its noble-metal character, Pd shows a considerable degree of chemical reactivity. In Pd Nanoparticles (NPs), atomic {Pdn+-X} states, where n = 0, 1, 2, 3, and X = atom or hydride, can play key roles in catalytic processes. Pd-oxygen moieties can be stabilized at nanointerfaces of Pd in contact with metal-oxides. These {Pdn+-X}s can be either isolated Pd atoms dispersed on the support, or, more interestingly, atomic states of Pd occurring on the Pd NPs. The present review focuses on the role of such {Pdn+-X} states in catalytic processes related to energy storage or energy conversion, with specific focus on photocatalysis, H2 production reaction (HRR), oxygen reduction reaction (ORR), and water-splitting. Synthesis of atomic {Pdn+-X} states and their detection methodology is among the current challenges. Herein, the chemistry of {Pdn+-X} states on Pd- [metal oxide] interfaces, methods of detection, and identification are discussed. The implication of {Pdn+-X} in transient catalytic intermediates is reviewed. Finally, the role of {Pdn+-X} in photo electrocatalytic processes is critically discussed.